Study of the inhibitory effect of Subtilis Bacillus isolated from Iraqi soil on some isolates of Staphylococcus aureus and Escherichia coli isolated from wounds and burns. (Journal of the College of Basic Education, 2023)
The study included the collection of (20) soil samples from different Iraqi soils from the governorates of Karbala, Najaf, Babil, as well as the capital, Baghdad, as it was possible to obtain (50) isolates belonging to the genus Bacillus. , Oxidase test, movement test, growth in anaerobic conditions, growth in (2%, 5%, 7%, 10%) of table salt, indole test, stearate consumption test as the only carbon source, Fox-Proscore test, ability to hydrolyze Starch, gas production from glucose sugar, as well as its ability to ferment (7) carbohydrate sources, where it was possible to obtain (8) isolates belonging to the type Bacillus subtilis, and the ability of the isolates to produce inhibitory substances when grown on nutritional broth at a temperature was tested. ((37 m) for a period of (4) days, then the filtrate of the grown isolates was concentrated in the liquid medium once and twice to increase its inhibition effectiveness. showed a According to the results, the unconcentrated Bacillus subtilis filtrates grown on Nutient broth have little inhibitory activity against Staphylococcus aureus isolates, which was shown by the Bacillus subtilis (1, 2, 4) and the filtrate of isolate 1-subtilis Bacillus did not give any significant inhibitory activity. Unconcentrated filtrates have no inhibitory activity against Escherichia coli isolates. The concentration of all bacteria filtrate once or twice showed its inhibitory effectiveness, as the concentrated filtrate had a high effectiveness in inhibiting the growth of Staphylococcus aureus isolates, while it had a lower inhibitory effectiveness against Escherichia coli isolates.